2016
DOI: 10.17511/ijpr.2016.i05.06
|View full text |Cite
|
Sign up to set email alerts
|

Clinicohematological profile of hemolytic anaemia in tertiary care hospital in rural Andhra Pradesh

Abstract: Introduction: Hemolytic anaemias are a group of disorders that cause significant morbidity in children. Method: A cross sectional study was conducted at NRI Medical College for a period of 1 year. All cases of newly diagnosed and old cases of hemolytic anaemia on follow up were included. Results: The study showed beta thalassemia as the most common hemolytic anaemia; followed by malaria, sickle beta thalassemia, thalassemia intermedia, beta thalassemia minor, Sickle cell disease, sickle cell trait, auto immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
1
1
1
Order By: Relevance
“…4 Present study observed the male to female ratio as 1.45 (59% male and 41% female), similar sex ratio of 1.51 (179 male and 118 female) is reported by to Chatopadhyay et al 5 Another study by Anusha R et al, reported 0.9 as male to female which could be due the study setup and sample section. 6 Current study noted the common HA's as beta thalassemia trait in 39.33%, followed by sickle cell anemia in 18.7% and beta thalassemia 16.67% subjects, similar observation were made in the study by Venkateshwary et al, they recorded thalassemia trait in 28.26% and thalassemia major in 16.45%. 7 Another study by Ambekar SS et al also found similar results where beta thalassemia trait was the most common HA.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…4 Present study observed the male to female ratio as 1.45 (59% male and 41% female), similar sex ratio of 1.51 (179 male and 118 female) is reported by to Chatopadhyay et al 5 Another study by Anusha R et al, reported 0.9 as male to female which could be due the study setup and sample section. 6 Current study noted the common HA's as beta thalassemia trait in 39.33%, followed by sickle cell anemia in 18.7% and beta thalassemia 16.67% subjects, similar observation were made in the study by Venkateshwary et al, they recorded thalassemia trait in 28.26% and thalassemia major in 16.45%. 7 Another study by Ambekar SS et al also found similar results where beta thalassemia trait was the most common HA.…”
Section: Discussionsupporting
confidence: 80%
“…7 Beta thalassemia had 16.7% cases with mean hemoglobin and HbF of 5.25gm/dl and 91% similar observation were made by Preethi et al, where the Hb ranged from 3-8.2 gm/dl, and HbF mean was 75.2%. Total serum bilirubin in the study was 3.75mg/dl which is higher than 2.7mg/dl recorded by Anusha R et al 6 In present study sickle cell trait cases were 2% of with mean Hb of 9.1 gm/dl. In Venkataswamy et al, sickle cell trait comprised of 1.55% of all cases with mean values of Hb as 10.8gm/dl.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation